Food security and nutrition monitoring for development: can India learn from international experience? - Babu, Suresh Chandra (International Food Policy Research Institute, 1996)
The food production-food security and nutrition relationship in India remains paradoxical after nearly three decades of food self-sufficiency. Malnutrition among the Indian pre-schoolers is nearly twice as high as in sub-Saharan Africa and more than three times as high as in China. Lack of information-based decision-making in designing food and nutrition policies is identified as a missing link in converting food self-sufficiency into nutritional well-being. Presenting institutional challenges for monitoring food security and nutritional status as an input in food and nutrition policy making, this paper examines the role of major food and nutrition monitoring systems that are in place in India for designing food and nutrition policies. The paper draws lessons from experiences within India as well as other countries, where several systems of monitoring the food security and nutritional status of the population have been successful in designing household food security and nutritional interventions.